Analysis of the Effect of Local Wisdom-Based Learning Modules on Student Learning Outcomes in the Implementation of the Merdeka Curriculum - Ni Wayan Karmini; Putri Anggreni; Ida Ayu Putu Sari; I Made Yudabakti; Ni Nyoman Wahyu Adi Gotama (International Journal of Language and Ubiquitous Learning, 2024)
Background. Learning based on local wisdom is gaining importance in education, especially within the Independent Curriculum, which allows adapting materials to local contexts. Modules based on local wisdom are believed to enhance student engagement and understanding, but empirical evidence regarding their effectiveness on learning outcomes remains limited. Purpose. This study aims to analyze the influence of the use of learning modules based on local wisdom on student learning outcomes in the implementation of the Independent Curriculum. Method. This study uses a quasi-experimental design involving two groups: an experimental group that uses a module based on local wisdom and a control group that uses a conventional module. The sample consisted of 200 students from four purposively selected junior high schools. The instruments used are learning outcome tests and attitude questionnaires. Results. Experimental group experienced significant improvements in cognitive, affective, and psychomotor learning outcomes compared to the control group. The average post-test scores of the experimental group were higher than those of the control group, with greater improvements in class engagement and positive attitudes towards learning. The use of modules based on local wisdom also strengthens students' ability to apply learning concepts into daily life, especially those related to local cultural values. Conclusion. Learning module based on local wisdom is effective in improving student learning outcomes and is relevant to the implementation of the Independent Curriculum. This approach not only improves academic understanding, but also supports the development of students' character and social skills.